Association between seropositivity for toxocariasis and cognitive functioning in older adults: an analysis of cross-sectional data from the US National Health and Nutrition Examination Survey (NHANES), 2011–2014. Issue 3 (1st March 2023) - Song, Ge; Yang, Chao; Qu, Zhe; Lin, Xuechun; Liu, Minhui; Wang, Yanhong
Abstract : Objectives: This study sought to examine the relationship between seropositivity for toxocariasis and cognitive functioning in a nationally representative sample of US older adults. Design: A cross-sectional study. Setting: National Health and Nutrition Examination Survey (NHANES) data collection took place in the US at participants' homes and mobile examination centres with specialised equipment. Participants: The study population consisted of 3188 community-dwelling US older adults aged 60 and above from the NHANES 2011 to 2014. Outcome measures: IgG antibody against Toxocara spp was tested by a Luminex assay using recombinant rTc-CTL-1 antigen. A value >23.1 mean fluorescence intensity (MFI) indicated positive for toxocariasis and a value ≤23.1 MFI as negative for toxocariasis. The Consortium to Establish a Registry for Alzheimer's Disease Word Learning subtest immediate and delayed memory, the Animal Fluency test and the Digit Symbol Substitution Test (DSST) were used to assess cognitive functioning. Cognitive test-specific and global cognitive z scores were computed using sample means and SD. Results: The study population consisted of 3188 participants who represented a total of 111 896 309 civilian citizens in the USA. The mean age of the participants was 69.6 years (standard deviation 6.8). The prevalence of toxocariasis in this population was 7.3% (95% confidence interval [CI] 6.1% to 8.5%). The survey-weighted linear regression model showed that compared with participants who were toxocariasis seronegative, those who were seropositive had lower DSST z score (beta [β] = −0.12, 95% CI −0.22 to −0.01) and global cognition z score (β=−0.11, 95% CI −0.22 to −0.01), after controlling for age, sex, race/ethnicity, education, depressive symptoms, smoking status, body mass index, prevalent coronary heart disease, prevalent stroke, and systolic blood pressure, physical activity, and total cholesterol. Conclusions: In our study, seropositive toxocariasis was independently and significantly associated with worse working memory, sustained attention, processing speed and global cognition in older adults. If this association is causal, public health measures to prevent human toxocariasis might help protect older adults' cognitive function.